Challenges and trends in wireless ubiquitous computing systems - Belghith, Abdelfettah (2014)
In the last decade, the Internet paradigm has been evolving toward a new frontier with the emergence of ubiquitous and pervasive systems, including wireless sensor networks, ad hoc networks, RFID systems, and wireless embedded systems. In fact, while the initial purpose of the Internet was to interconnect computers to share digital data at large scale, the current tendency is to enable ubiquitous and pervasive computing to control everything anytime and at a large scale. This new paradigm has given rise to a new generation of networked systems, commonly known as Internet-of-Things or Cyber-Physical Systems.